Системы контроля металлорежущего оборудования - Набока, Елена Владимировна; Приходько, Ольга Юрьевна (НТУ "ХПИ", 2012)
В статье рассмотрено применение современных систем контроля металлорежущего оборудования с целью повышения качества обработки детали. The paper considers the use of modern control systems of cutting equipment in order to improve the quality of the parts.

Provides information on the impact of design features of equipment for thermochemical and thermal-pulse processing complex-area detail on the application of advanced technologies, as well as a classification of materials, the relative energy intensity of production processes, depending on the optimum treatment time and temperature on the thickness of the elements and the elimination of parts. An algorithm is also facilities for termal-pulse process that implements the safe operation and automatic selection modes.
Keywords: контактные датчики; щуп; система передачи данных; интерфейсные адаптеры; программное обеспечение; модули датчика; оптические модули; focusing prod; transmitter; measuring system; instrument; controller